Septic shock diagnosis and its treatment - Reshi, Mohd Rafi; Nabi, Nusrat; Muzaffar, Muzamil; Anees, Saman; Yusuf, Nausheen; Qasim, Atiya; Naqvi, Maaz (International Journal of Basic & Clinical Pharmacology, 2024)
In critical care, sepsis continues to be a major cause of mortality. The pathogenic, diagnostic, and therapeutic panorama of sepsis is no longer restricted to the critical care unit: many patients who enter treatment through other doors, both inside and outside the hospital, develop severe illness. Next, administer fluids and broad-spectrum antibiotics after taking the proper cultures. Step up the treatment to include monitoring urine output, blood gases for base excess, lactate, haemoglobin, and glucose if the situation does not get better within the following six hours. These will dictate how bicarbonate, insulin, fluids, transfusions, and vasopressors are managed. The patient should be sent to intensive care if the hypotension doesn’t improve (septic shock). Sepsis can now be treated with methods that have produced better results with other illnesses. New medicines have been created as a result of a better understanding of the biology of severe sepsis and septic shock, placing a strong emphasis on early detection and aggressive treatment. The major priorities continue to be prevention through screening, preventing cross infection, and prudent antibiotic usage.